2017
DOI: 10.1186/s12936-016-1651-5
|View full text |Cite
|
Sign up to set email alerts
|

Malaria epidemiology in central Myanmar: identification of a multi-species asymptomatic reservoir of infection

Abstract: BackgroundThe spread of artemisinin-resistant Plasmodium falciparum is a global health concern. Myanmar stands at the frontier of artemisinin-resistant P. falciparum. Myanmar also has the highest reported malaria burden in Southeast Asia; it is integral in the World Health Organization’s plan to eliminate malaria in Southeast Asia, yet few epidemiological data exist for the general population in Myanmar.MethodsThis cross-sectional, probability household survey was conducted in Phyu township, Bago Region (centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
1
54
1
Order By: Relevance
“…Plasmodium vivax was the most prevalent species among asymptomatic cases in this study, similar to the distribution of malaria species reported in other works [11, 12]. However, a recent study in central Myanmar reported the low prevalence of asymptomatic malaria infection, with a predominance of P. falciparum [28]. The difference likely reflects the heterogeneity of malaria species distribution in central Myanmar.…”
Section: Discussionsupporting
confidence: 88%
“…Plasmodium vivax was the most prevalent species among asymptomatic cases in this study, similar to the distribution of malaria species reported in other works [11, 12]. However, a recent study in central Myanmar reported the low prevalence of asymptomatic malaria infection, with a predominance of P. falciparum [28]. The difference likely reflects the heterogeneity of malaria species distribution in central Myanmar.…”
Section: Discussionsupporting
confidence: 88%
“…To overcome cross-amplification of P. vivax isolates with ribosomal gene PCR assays [3, 19], Ghinai et al [30] have recently described a PCR-sequencing approach to detect P. knowlesi cytb DNA, which also provided satisfactory sensitivity. However, our sicavar target assay provides greater sensitivity for P. knowlesi identification in our hands and was effective in detecting submicroscopic parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Age of individuals included in the analysis was divided into four groups: under 5 years (reference category), 5-14 years, 15-64 years, and 65+ years. This breakdown was motivated by the literature (38)(39)(40) that often show distinct differences in malaria prevalence across these age groups. Many data sources speci cally sample children under 5, because they often bear the highest malaria mortality (41).…”
Section: Malaria Outcome and Associated Socioeconomic And Demographicmentioning
confidence: 99%